Beneficiaries and cost bearers: evidence on political clientelism from Hungary. Issue 1 (2nd January 2022) - Vasvári, Tamás
ABSTRACT: Previous research has found that there is no uniform budget constraint for local governments: politically favoured local governments receive additional funds and are subject to less fiscal discipline. If so, the fair distribution between beneficiaries and cost bearers of the local fiscal policy is not realised. The paper focuses on this phenomenon in the light of political clientelism. We conduct an analysis regarding the Hungarian local government system between 2006 and 2018 to capture the political patterns in local fiscal policy and central granting policy. Local governments in opposition were underfinanced in terms of discretionary and EU funds, and since 2012 they have also had limited access to credit markets to obtain additional funds. Favoured municipalities enjoy more funds and can deliver more projects to their citizens – at the expense of unfavoured ones. The latter struggle to establish a fair distribution of the burdens between beneficiary generations.